Carbon nano horn and bovine serum albumin hierarchical composite: towards bio-friendly superhydrophobic protein film surfaces - Jadhav, Anil D.; Ogale, Satishchandra B.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
Highly hydrophilic glass substrates when coated with films of carbon nano horns dispersed in the ubiquitous protein bovine serum albumin display hydrophobic characteristics. Incidentally both the materials used to create the final hydrophobic surface are known to be highly bio-compatible. The features observed are accredited to the replication of the micro and nanoscale hierarchical structures of carbon nano horns in the final film composite.

Chemical inhomogeneity and mixed-state ferromagnetism in diluted magnetic semiconductor Co : TiO2 - Ogale, Satishchandra B.; Kundaliya, Darshan; Mehraeen, Shareghe; Fu, Lian-feng; Zhang, Shixiong; Lussier, Alexandre; Dvorak, Joe; Browning, Nigel D.; Idzerda, Yves; Venkatesan, Thirumalai (Chemistry of Materials, 2008)
Diluted magnetic semiconductors (DMS) are among the most intensely investigated materials in recent times in view of their great application potential. Yet, they are also the most controversial because of the possibility of extrinsic effects attributable to dopant solubility and clustering, point defects, incorporation of unintentional impurities, etc. This has highlighted the central role of materials chemistry in rendering a specific microstate and property response. In this work, we provide a combined window of high-resolution scanning transmission electron microscopy and electron energy-loss spectrometry, X-ray absorption (XAS)/X-ray magnetic circular dichroism (XMCD), and magnetization measurements on epitaxial rutile CoxTi1-xO2 (x = 0-0.06) system (the first discovered oxide-DMS, which continues to be controversial) grown at low temperature (400 degrees C) under different ambient atmospheres. The study brings out a mixed-state scenario of ferromagnetism involving intrinsic DMS (uniform dopant distribution at low dopant concentration) and coupled cluster magnetism, involving cobalt associations within the matrix at higher concentrations. We also show that by matrix valence control during growth, it is possible to realize a uniform embedded cluster state and the related coupled cluster magnetism.

Co : CdS diluted magnetic semiconductor nanoparticles: radiation synthesis, dopant-defect complex formation, and unexpected magnetism - Bogle, Kashinath A.; Ghosh, Saurabh; Dhole, Sanjay D.; Bhoraskar, Vasant N.; Fu, Lian-feng; Chi, Miao-Fang; Browning, Nigel D.; Kundaliya, Darshan; Das, Gour P.; Ogale, Satishchandra B. (Chemistry of Materials, 2008)
Incorporating a dopant into a nanoparticle is a nontrivial proposition in view of the size dependent surface versus bulk energy considerations and the intrinsic proximity of the surface to the interior, which facilitates migration to the surface. If realized and controlled, however, it can open up new avenues to novel nanomaterials. Some previous studies have shown the dopability of nanosystems but only with specific surface functionalization. Here, we demonstrate the successful dopant incorporation via a new route of pulsed high energy electron induced synthesis. We choose a system Co:CdS (dilutely cobalt doped cadmium sulfide) in view of the well-known application-worthy properties of CdS and the potential possibility of its conversion to a diluted magnetic semiconductor of interest to spintronics. By using various techniques, we show that matrix incorporation and uniform distribution of cobalt are realized in US nanocrystals without the need for additional chemical or physical manipulation. Optical and photoluminescence properties also support dopant incorporation. Interestingly, although magnetism is realized, it is weak, and it decreases at higher cobalt concentration. First principle density functional calculations are performed to understand this counterintuitive behavior. These calculations suggest that the introduction of parent cation or anion vacancies lead to magnetic moment reduction, albeit marginally. However, with some Co impurity fraction in the octahedral interstitial site inside the wurtzite cage, the magnetic moment drops down drastically. This study reveals that defect states may have an interesting role in dopant stabilization in nanosystems, with interesting system dependent consequences for the properties.

Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Chlorate ion mediated rutile to anatase reverse phase transformation in the TiO2 nanosystem - Bhosale, Reshma; Hyam, Rajeshkumar S.; Dhanya, P.; Ogale, Satishchandra B. (Dalton Transactions, 2011)
Rutile TiO2 nanoneedles (8 nm x 100 nm) synthesized at room temperature by anodization in perchloric acid (pH < 1) are shown to undergo an interesting reverse phase transformation to anatase nanoparticles (8 nm) at 300 degrees C only if the chlorate ions are maintained in the ambient medium. When chlorate ions are removed by multiple washing, the rutile phase and the needle morphology are maintained. The mechanism of formation of the ion-stabilized solid and its thermal evolution is discussed.

Carbon nanoscrolls by pyrolysis of a polymer - Yadav, Prasad; Warule, Sambhaji; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2012)
3D network of carbon nanoscrolls was synthesized starting from pyrolysis of poly(acrylic acid-co-maleic acid) sodium salt. It is a catalyst-free process where pyrolysis of polymer leads to formation of carbon form and sodium carbonate. Upon water soaking of pyrolysis product, the carbon form undergoes self-assembly to form carbon nanoscrolls. The interlayer distance between the walls of carbon nanoscroll was found to be 0.34 nm and the carbon nanoscrolls exhibited a surface area of 188 m(2)/g as measured by the BET method. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanoscrolls; Polymer; Pyrolysis; supercapacitor

Characterization of biocompatible NiCo2O4 nanoparticles for applications in hyperthermia and drug delivery - Kale, Sangeeta N.; Jadhav, Anil D.; Verma, Seema; Koppikar, Soumya J.; Kaul-Ghanekar, Ruchika; Dhole, Sanjay D.; Ogale, Satishchandra B. (Nanomedicine-Nanotechnology Biology and Medicine, 2012)
Monodispersed, superparamagnetic nickel cobaltite (NCO) nanoparticles were functionalized using mercaptopropionic acid (MPA). MPA conjugates with NCO forming a metal-carboxylate linkage, with the MPA-MPA interaction occurring via formation of disulfide bonds, leaving another carboxyl end free for additional conjugation. The cytotoxicity studies on NCO-MPA show cell viability of similar to 100% up to a dosage of 40 mu g/mL on SiHa, MCF7, and B16F10 cell lines, and on mouse primary fibroblasts. Time-dependent cell viability studies done for a duration of 72 hours showed the cell lines' viability up to 80% for dosages as high as 80 mu g/mL. Negligible leaching (<5 ppm) of ionic Co or Ni was noted into the delivery medium. Upon subjecting the NCO-MPA dispersion (0.1 mg/mL) to radiofrequency absorption, the nanoparticles were heated to 75 degrees C within 2 minutes, suggesting its promise as a magnetic hyperthermia agent. Furthermore, the amino acid lysine and the drug cephalexin were successfully adducted to the NCO system, suggesting its potential for drug delivery. From the Clinical Editor: NCO-MPA nanopartciles were found to be promising magnetic hyperthermia agents, suggesting potential future clinical applications. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cytotoxicity; drug delivery; Magnetic hyperthermia; Magnetic nanoparticles

CH3NH3Pb(BF4)(3) and (C4H9NH3)2Pb(BF4)(4) family of 3D and 2D perovskites without and with iodide and bromide ions substitution - Nagane, Satyawan; Ogale, Satishchandra B. (Journal of Physical Chemistry Letters, 2016)
We report the synthesis of fully molecular ion (BF4 )-based organicinorganic hybrid perovskite CH3NH3Pb(BF4)(3), which is a wide band gap semiconductor, and the same can be easily tuned toward the visible by the incorporation of bromide or iodide ions in the crystal framework simply by changing lead precursors. We have also successfully transformed the distorted 3D molecular-ion-induced perovskite to 2D (C4H9NH3)(2)Pb(BF4)(4), (C4H9NH3)(2)PbBr(4x)(BF4)(x), and (C4H9NH3)(2)PbI(4x)(BF4)(x) perovskites that exhibit the optical absorption over the UV to visible region. The thin films of molecular-ion-containing 2D perovskites with Br and I anions show blue and green luminescence, respectively, under UV illumination.

CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.